Fiscal vertical imbalance and income inequality: A threshold effect analysis based on government expenditure. - Lan Mao (PLoS ONE)
This study aims to investigate the complex relationship between vertical fiscal imbalance, public expenditure structure, and income distribution disparities, with the goal of providing policy insights for achieving shared prosperity. Employing Generalized Method of Moments (GMM) and threshold analysis, the research reveals key findings: (1) an exacerbation of vertical fiscal imbalance significantly widens the urban-rural income gap; (2) public expenditure structure exhibits threshold effects, resulting in non-linear impacts on income disparity; (3) a unique contribution of our study is the identification of varying threshold effects of urban public expenditure on income disparities within rural areas, urban areas, and the gap between them, underscoring the need for targeted fiscal interventions. These findings highlight the critical role of public expenditure in addressing income distribution issues and offer valuable guidance for upcoming fiscal and tax reforms.